Impatiens megamalayana, a new species of Impatiens from the Western Ghats, Tamil Nadu, India - Ramasubbu, R.; Divya, C.; Kala, N. Sasi; Surendran, Anjana; Sreekala, A.k. (Phytotaxa, 2017)
Impatiens megamalayana, a new species from Tamil Nadu, India is described and illustrated. This species is characterized by a ridged stem, ensiform and villous leaves, a wrinkled boat-shaped lower sepal with outwardly curved tip, ornamented seeds and strictly ovate pollen grains. This combination of characters makes determining the relationships of I. megamalayana difficult. The floral structure of I. megamalayana is closely allied to I. herbicola Hook.f. and I. inconspicua Benth. in Wall., the latter with three varieties, but it differs by several unique vegetative and floral features. Impatiens megamalayana is assessed as Critically Endangered in accordance with the IUCN guidelines. The habitat of the species is severely affected by landslides. As a result, effective strategies should be developed to protect I. megamalayana from exinction.